Peningkatan Hasil Belajar IPS melalui Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw pada Siswa Kelas VII.A SMP Islam Khadijah Bagik Nyaka - Muslim, Bukhari (YASIN, 2023)
This kind of study is regard to Classroom Action Research (CAR) which the target are 29 female student’s seventh grade A Class Islamic Junior High School Khadijah Bagek Nyaka. This study aim to find how far of study result development Social Science subject with applicate Study Mod Cooperative Jigsaw Type. This study conducted in 2 cycle, from action result that conducted is approved able to increasing study result with reaching classical completeness set in 85 %. Classical completeness 48,82 % obtained in the first cycle with average value 67,59. They able to increased it at seconf stage by 96,55 % with average 86,90. From activity side there are enhancement as well, its obtained in the first cycle from mild active category to very active category. Result of this study provide that applicate of Study Mod Cooperative Jigsaw Type able to increasing student study result in Social Science subject with completeness reach 96,55 %.